Strategi Pendampingan Muallaf Dalam Pembelajaran Metode Iqro’ dan Al-Qur’an di Tembilahan Kabupaten Indragiri Hilir - Nur, Syamsiah; Siagian, Seri Yanti; Zariah, Siti (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
The accompaniment strategy for muallaf (new converts to Islam) in understanding and practicing Islamic teachings plays a crucial role in building their Islamic identity. This program aims to provide guidance in reading the Qur’an using the Iqro’ method and to introduce fundamental Islamic values to muallaf in Tembilahan, Indragiri Hilir Regency. With a systematic approach tailored to individual needs, this program is expected to enhance the muallaf’s ability to read the Qur’an, strengthen their understanding of Islam, and offer the necessary social support during their adaptation process. The results of this community service activity successfully delivered effective guidance for muallaf in reading the Qur’an through the Iqro’ method and reinforced their comprehension of basic Islamic principles